Tumour Marker Requisition Pattern in a Tertiary Care Centre of Eastern Nepal - Niraula, A.; Gelal, B.; Chaudhari, R. K.; Das, B. K. L.; Lamsal, M. (Kathmandu University Medical Journal, 2022)
Background Tumor markers have been a valuable tool for decades to aid in the diagnosis, treatment, and monitoring of oncological diseases. Objective To retrospectively analyze the requisition pattern of tumor marker requests at the largest tertiary care center in eastern Nepal. Method A retrospective hospital-based cross-sectional study was conducted to obtain the data for 5 common tumor markers i.e., Alpha-Fetoprotein (AFP), Cancer antigen- 125 (CA-125), Carbohydrate antigen (CA) 19-9, Carcinoembryonic antigen (CEA), and Prostate-specific antigen (PSA) analyzed in the Department of Biochemistry at B.P. Koirala Institute of Health Sciences, Dharan, Nepal for 5 years. Result A total of 8716 tests for tumor marker was conducted over 5 years. The most common tumor marker requested at our hospital was Prostate-specific antigen (48.77%) followed by Cancer antigen-125 (39.02%), Carcinoembryonic antigen (9.30%), Alpha-Fetoprotein (2.29%), and Carbohydrate antigen 19-9 (0.63%) respectively. The majority of the tumor markers (Alpha-Fetoprotein, Cancer antigen-125, Carbohydrate antigen 19-9, and Carcinoembryonic antigen) were requested from in-patient wards while Prostate-specific antigen was majorly requisitioned from the out-patient department (OPD) [74%] respectively. Conclusion The finding from the present study suggest that though Nepal is one of the developing countries where the specialized health care services are limited only to cities and developed areas, the burden of oncological disease is high. Dharan is one of the small cities in the eastern part of Nepal and serves the majority of the population in the periphery. The number of tumor marker requisitions as per the laboratory data is significant (n=8716) over a period of 5 years where few tests like Alpha-Fetoprotein, Carcinoembryonic antigen, and Carbohydrate antigen 19-9 have just been initiated. Also, the findings delineate that the outpatient departments have requested more tumor markers which might/ might not be inconsistent with the preliminary diagnosis.